Respuesta :
Michael is required to solve the systems of equation
He made his first error in step 1
Michael's calculation:
3x – 3y = 6
4x – 7y = 2
Step 1: 4(3x – 3y = 6) –3(4x – 7y = 2)
Step 2: 12x – 12y = 24 –12x + 21y = –6
Step 3: 9y = 18
Step 4: y equals 1 over 2
Correct calculation:
3x – 3y = 6 (1)
4x – 7y = 2 (2)
make x the subject in ....(1)
3x - 3y = 6
3x = 6 + 3y
x = 6 + 3y/ 3
x = 2 + y
substitute x = 2 + y into (2)
4x – 7y = 2 (2)
4(2 + y) - 7y = 2
8 + 4y - 7y = 2
8 - 3y = 2
8 + 2 = -3y
10 = -3y
y = 10/-3
y = -3 1/3
Read more:
https://brainly.com/question/2159099
Answer:
The correct answer is that there is an error in STEP 2
Step-by-step explanation:
I took the test and I got this question correct!